Talking out the taboo : Unraveling sex and how it evolves during pregnancy - Abigail Rembui, Jerip; Tan, Cheng Siang; Awi, Idi; Andy Bong, Cheong Shin; Yee, Yee Kyaing (Malaysian Medical Association (MMA), 2024)
ABSTRACT Introduction: In the strive to amend inequalities, the sustainable developmental goals (SGD) and declared objective of leaving no one behind are praised for their paradigm-shifting potential, particularly concerning sexual reproductive health (SRH), SDG Number 3.7. However, in-depth questions of bedrock origins that perpetuate this unbalanced progress are sparse and superficial at best, especially in Southeast Asian (SEA) communities. It was clear throughout research into peripartum and postpartum high-risk Human Papilloma Virus (hrHPV) infection, that sex-related questions are avoided, despite the clinical setting. Objective: The study aimed to identify a perceptive manner to talk about how and why sex evolved around pregnancy. Materials and Methods: Postnatal women in Sarawak General were privately interviewed from September to December 2023 (n=416) regarding intercourse frequency before and during pregnancy and asked a reason for these changes. Their facial expressions, answers or lack thereof and body language were noted. Results: Questions were met with embarrassed or avoidant behaviour, dismissive replies and an urgency to move on; similarly, the postpartum resumption of sex and contraception discussion. The data showed a significant reduction in intercourse during pregnancy, citing fear for the fetus as the main reason and the husband feeling pity for the pregnant wife as a close second. Rarely are the woman’s needs mentioned, highlighting that female libido is still unspoken of in Asian cultures. Conclusion: It is taboo enough to talk about sex with married multiparous women, what more the stigmatised and marginalised groups. This paper dives into safe sexual relationships in pregnancy and how SRH topics can be perceptively discussed in religious and conservative communities.